Induction of somatopause in adult mice compromises bone morphology and exacerbates bone loss during aging. Issue 12 (23rd November 2021) - Dixit, Manisha; Duran‐Ortiz, Silvana; Yildirim, Godze; Poudel, Sher Bahadur; Louis, Leeann D.; Bartke, Andrzej; Schaffler, Mitchell B.; Kopchick, John J.; Yakar, Shoshana
Abstract: Somatopause refers to the gradual declines in growth hormone (GH) and insulin‐like growth factor‐1 throughout aging. To define how induced somatopause affects skeletal integrity, we used an inducible GH receptor knockout (iGHRKO) mouse model. Somatopause, induced globally at 6 months of age, resulted in significantly more slender bones in both male and female iGHRKO mice. In males, induced somatopause was associated with progressive expansion of the marrow cavity leading to significant thinning of the cortices, which compromised bone strength. We report progressive declines in osteocyte lacunar number, and increases in lacunar volume, in iGHRKO males, and reductions in lacunar number accompanied by 20% loss of overall canalicular connectivity in iGHRKO females by 30 months of age. Induced somatopause did not affect mineral/matrix ratio assessed by Raman microspectroscopy. We found significant increases in bone marrow adiposity and high levels of sclerostin, a negative regulator of bone formation in iGHRKO mice. Surprisingly, however, despite compromised bone morphology, osteocyte senescence was reduced in the iGHRKO mice. In this study, we avoided the confounded effects of constitutive deficiency in the GH/IGF‐1 axis on the skeleton during growth, and specifically dissected its effects on the aging skeleton. We show here, for the first time, that induced somatopause compromises bone morphology and the bone marrow environment. Abstract : Induced somatopause during aging causes a drop in GH/IGF‐1 signaling, inhibits radial bone expansion and associates with increased bone marrow adiposity. At the bone tissue level, induced somatopause leads to progressive declines in osteocyte lacunar density and connectivity.